Analysis of Customer’s Attitudes of Tempeh Product in Mataram City - Muhamad Ilhamudin; Masrun (ProBisnis : Jurnal Manajemen, 2023)
The research is aimed at determining the customer‘s attitude towards product tempeh of Mataram city, which is produced at Pejeruk Abian. The research is descriptive which using sample survey method. In order to answer the problem proposed, the analytical tool is Ideal-Point Model. The model measures a difference between what is desired and what is perceived by consumers. The result of this study shows that consumers provide a very good assessment to the existing attributes. It means that customer’s attitude to the product is very good which is in accordance with consumer’s desire.